La precarietà giuridica ed esistenziale delle persone straniere in Italia (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The article analyzes the impact of Italian migration policies on the legal, existential, and health conditions of foreign nationals, highlighting how legal fragmentation and administrative practices generate structural insecurity and inequalities in access to fundamental rights. Using the framework of the social determinants of health, it underscores how precarious legal status—shaped by political choices, arbitrary classifications, and restrictive mechanisms of entry and residence—negatively affects migrants’ physical and psychological well-being. The exclusion from, or conditional access to, social rights—particularly the right to health and stable employment—exposes migrants to systemic vulnerability, marginalization, and exploitation. This resulting “legal poverty” emerges not only as a limitation of self-determination but also as a concrete risk factor for individual and collective health.
Keywords: Migration status; Legal precariousness; Institutional discrimination; Social determinants of health; Existential vulnerability